Assessment of Field-in-Field, 3-Field, and 4-Field Treatment Planning Methods for Radiotherapy of Gastro-Esophageal Junction Cancer - Ghazal Mehri-Kakavand; Mohamad Pursamimi; Wrya Parwaie; Mahdi Ghorbani; Mehdi Khosrav; Seyyed Mohammad Hosseini; Ali Soleimani Meigooni (Journal of Biomedical Physics and Engineering, 2022)
Background: Gastro-esophageal (GE) junction cancer is the fastest-growing tumor, particularly in the United States (US). Objective: This study aimed to compare dosimetric and radiobiological factors among field-in-field (FIF), three-field (3F), and four-field box (4FB) radiotherapy planning techniques for gastro-esophageal junction cancer.Material and Methods: In this experimental study, thirty patients with GE junction cancer were evaluated, and three planning techniques (field-in-field (FIF), three-field (3F), and four-field box (4FB)) were performed for each patient for a 6-MV photon beam. Dose distribution in the target volume, the monitor units (MUs) required, and the dose delivered to organs at risk (OARs) were compared for these techniques using the paired-sample t-test. Results: A significant difference was measured between the FIF and 3F techniques with respect to conformity index (CI), dose homogeneity index (HI), and tumor control probability (TCP) for the target organ, as well as the Dmean for the heart, kidneys, and liver. For the spinal cord, the FIF technique showed a slight reduction in the maximum dose compared to the other two techniques. In addition, the V20 Gy of the lungs and the normal tissue complication probability (NTCP) of all OARs were reduced with FIF method.  Conclusion: The FIF technique showed better performance for treating patients with gastro-esophageal junction tumors, in terms of dose homogeneity in the target, conformity of the radiation field with the target volume, TCP, less dose to healthy organs, and fewer MU.